Corona de Castilla-Corona de Aragón - José Ignacio Fortea Pérez (Mélanges de la Casa de Velázquez)
This article is intended as a comparative study of the course of institutional, social and political development in the regimes of municipal government in the Crown of Castile and the Crown of Aragon throughout the Modern Age. The obvious differences between the models of institutional organisation of urban government typical of either kingdom are clearly identified, but the study also highlights the similarities of the principles underlying either model, and the convergence of the objectives that they pursued. The study also analyses the processes, having their own specific forms in either territory, that brought about the formation of a municipal oligarchy which was socially heterogeneous in origin but progressively achieve cohesion around common values, properties and ways of life. Finally, the article examines the principles inspiring the Crown and the objectives that it pursued in its relations with local power elites in the municipalities of the two Crowns.